A senescence-based prognostic gene signature for colorectal cancer and identification of the role of SPP1-positive macrophages in tumor senescence - Yu, Sifei; Chen, Mengdi; Xu, Lili; Mao, Enqiang; Sun, Silei (Frontiers in Immunology, 2023)
Background: Senescence is significantly correlated with the prognosis of cancer. Our study aimed to construct a senescence-related prognostic model in colorectal cancer (CRC) cancer and investigate the influence of senescence on tumor microenvironment. Methods: Transcriptome and clinical data of CRC cases were downloaded from TCGA and GEO databases. Senescent-related prognostic genes detected by univariable cox regression were included in the LASSO analysis to construct the model. The efficacy of the model was validated by the ROC curve and survival analysis. Differentially expressed genes (DEGs) were identified. GO and KEGG pathway enrichment were performed. CIBERSORT and Immuno-Oncology-Biological-Research (IOBR) were used to investigate the tumor microenvironment features. Single cell RNA-seq data were used to investigate the expression level of model genes on various cell types. Immunofluorescence staining against p21, SPP1 and CD68 was performed in human colon tissues. Results: A seven-gene (PTGER2, FGF2, IGFBP3, ANGPTL4, DKK1, WNT16 and SPP1) model was finally constructed. Patients were defined as high-risk and low risk using the median score as threshold. The AUC for 1-, 2-, and 3-year disease-specific survival (DSS) were 0.731, 0.651 and 0.643, respectively. Survival analysis showed a better 5-year DSS in low-risk patients in the construction cohort and the validation cohorts. GO and KEGG analysis revealed that DEGs were enriched in ECM-receptor interaction, focal adhesion and protein digestion and absorption. CIBERSORT and IOBR analysis showed that abundance of macrophages and an immunosuppressive environment in the high-risk subgroup. Low-risk patients had higher response rates to immunotherapy. ScRNA-seq data revealed the high expression of SPP1 on a subset of macrophages and this subset had strong SASP features. Using CRC tumor tissues, we discovered that SPP1+ macrophages were surrounded by a large number of senescent tumor cells in high-grade tumors. Conclusion: Our study presented a novel model based on senescence-related genes which could identify CRC patients with poor prognosis and immunosuppressive tumor microenvironment. SPP1+ macrophages might correlate with cell senescence and lead to poor prognosis.